2012
DOI: 10.1155/2012/329796
|View full text |Cite
|
Sign up to set email alerts
|

The Synthesis of Anatase Nanoparticles and the Preparation of Photocatalytically Active Coatings Based on Wet Chemical Methods for Self-Cleaning Applications

Abstract: We report on an improved sol-gel method for the production of highly photocatalytic titanium dioxide (TiO 2 ) anatase nanoparticles which can provide appropriate control over the final characteristics of the nanoparticles, such as particle size, crystallinity, crystal structure, morphology, and also the degree of agglomeration. The synthesized anatase nanoparticles were characterized using various techniques, such as X-ray powder diffraction (XRD), scanning electron microscopy (SEM), and transmission electron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…The results indicated that low-temperature calcination can improve crystallinity and crystallite size of the as-synthesized TiO 2 powders. However, only a slight increase of crystallinity and crystallite sizes were observed for the powders calcined at 200 C, 300 C and 400 C. These results are in good agreement with previous reported studies which shows that only small changes in the crystallinity and the crystallite sizes of the TiO 2 powders were observed when the powders were calcined below 500 C 3,15) . Moreover, the XRD results were consistent with the DTA result as the curve also revealed that no temperature-induced phase transition occurred when the temperature was increased up to 400 C. Despite the fact that the transformation of anatase to rutile is above 700 C 12,15,16) and only anatase phase was identi ed even after the post-heat treatment.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The results indicated that low-temperature calcination can improve crystallinity and crystallite size of the as-synthesized TiO 2 powders. However, only a slight increase of crystallinity and crystallite sizes were observed for the powders calcined at 200 C, 300 C and 400 C. These results are in good agreement with previous reported studies which shows that only small changes in the crystallinity and the crystallite sizes of the TiO 2 powders were observed when the powders were calcined below 500 C 3,15) . Moreover, the XRD results were consistent with the DTA result as the curve also revealed that no temperature-induced phase transition occurred when the temperature was increased up to 400 C. Despite the fact that the transformation of anatase to rutile is above 700 C 12,15,16) and only anatase phase was identi ed even after the post-heat treatment.…”
Section: Resultssupporting
confidence: 92%
“…These hard agglomerated particles, which have less porosity, were dif cult to fracture upon impact during the deposition as the particles were strongly bonded together. These strong bonds, which are formed by the crystalline bridges 3) between the particles, made them resistant to fragmentation and adherence on surface of the substrate. This result also shows that a further increase of post heat treatment temperature on as-synthesized TiO 2 powders; at 400 C and above lead to dif culties in building up the coating during collision, and this nding is in good agreement with previous study reported by Salim et al 12) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While the surface charge measured for amorphous nanocapsules was negative, the anatase homologue unexpectedly showed a positive surface charge. Generally, the surface charge depends on the pH, 48 which was close to pH 7 as the Ag-TiO 2 formulations were dispersed in water. Interestingly, it has been shown that depending on the precursors used to generate titania, on the surfactant and on the heat treatment, the surface charge can indeed become positive even at pH 7.…”
Section: Discussionmentioning
confidence: 99%
“…These properties make TiO 2 an attractive candidate for its utilization as a photocatalyst in the photocatalytic processes. TiO 2 has been extensively studied and demonstrated to be suitable for numerous applications such as, destruction of microorganisms [2][3][4][5], inactivation of cancer cells [6,7], protection of the skin from the sun [8][9][10][11], photocatalytic water splitting to produce hydrogen gas [12][13][14], manufacture of some drug types [15][16][17], degradation of toxic organic pollutants in water [18][19][20], and self-cleaning of glass and ceramic surfaces [21]. Even though TiO 2 is the most used semiconductor material, it exhibits some disadvantages, such as low surface area and fast recombination rate between the photogenerated charge carriers and the maximum absorption in the ultraviolet light region.…”
Section: Introductionmentioning
confidence: 99%